The ascertainment of customary law: What is ascertainment of customary law and what is it for? - Manfred O Hinz (Oñati Socio-Legal Series, 2012)
Traditional communities are no longer homogeneous. Before, basically everybody knew what the law of the community was. There is a growing understanding that the legal complexity experienced in urban settlements where various customary laws apply needs attention. There is also a growing acceptance that the verdict of the chief is not necessarily the last word: dissatisfied parties may take that verdict on appeal to a state court whose judges will not necessarily know what the customary law applied by the court a quo.